2014
DOI: 10.1073/pnas.1404047111
|View full text |Cite
|
Sign up to set email alerts
|

XerD-mediated FtsK-independent integration of TLCϕ into the Vibrio cholerae genome

Abstract: As in most bacteria, topological problems arising from the circularity of the two Vibrio cholerae chromosomes, chrI and chrII, are resolved by the addition of a crossover at a specific site of each chromosome, dif, by two tyrosine recombinases, XerC and XerD. The reaction is under the control of a cell division protein, FtsK, which activates the formation of a Holliday Junction (HJ) intermediate by XerD catalysis that is resolved into product by XerC catalysis. Many plasmids and phages exploit Xer recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
64
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(64 citation statements)
references
References 28 publications
0
64
0
Order By: Relevance
“…In all of the reported cases, integration of IMEXs recreates a bona fide dif site, thereby not interfering with chromosome dimer resolution, which would lead to their counter-selection. The best-described examples are Vibrio cholerae IMEXs, which carry crucial virulence determinants (5)(6)(7)17). These IMEXs have developed different strategies to integrate and to remain stably integrated, although the mechanisms ensuring their stable maintenance are not fully understood.…”
mentioning
confidence: 99%
“…In all of the reported cases, integration of IMEXs recreates a bona fide dif site, thereby not interfering with chromosome dimer resolution, which would lead to their counter-selection. The best-described examples are Vibrio cholerae IMEXs, which carry crucial virulence determinants (5)(6)(7)17). These IMEXs have developed different strategies to integrate and to remain stably integrated, although the mechanisms ensuring their stable maintenance are not fully understood.…”
mentioning
confidence: 99%
“…4). Like CTX, both the phages use the same host-encoded XerC and XerD recombinases, but their integration in the chromosome of the cholera pathogen relies on the double-stranded attP substrates (25,26). We observed that integration of VGJ and TLC is not increased in lexA (Ind Ϫ ) V. cholerae cells (Table 5).…”
Section: Conjugationmentioning
confidence: 81%
“…The attachment site of a V. cholerae IMEX, the toxin-linked cryptic phage (TLCϕ) harbors four of these bases (Fig. 1D, blue bases of dif GGI3 and attP TLC ) (25). We previously demonstrated that XerD poorly bound to attP TLC , which is sufficient to prevent XerD-mediated FtsK-dependent recombination (25).…”
mentioning
confidence: 98%
“…1D, blue bases of dif GGI3 and attP TLC ) (25). We previously demonstrated that XerD poorly bound to attP TLC , which is sufficient to prevent XerD-mediated FtsK-dependent recombination (25). Thus, it is tempting to propose that GGI are IMEX and dif GGI sites were selected not only to escape but also to overcome the normal cellular control imposed on Xer recombination by FtsK.…”
mentioning
confidence: 99%
See 1 more Smart Citation